Salidroside Prevents Hypoxia-Induced Human Retinal Microvascular Endothelial Cell Damage Via miR-138/ROBO4 Axis - Shi, Xiaoling (Invest Ophthalmol Vis Sci, 2021)
PURPOSE: Retinopathies are associated with the injury of retinal microvascular endothelial cells. Salidroside (SAL) is a medicinal supplement that has antioxidative and cytoprotective properties. We hypothesized that SAL might have a protective function in retinopathies. This research aims to explore the function and mechanism of SAL in hypoxia-induced retinal microvascular endothelial cell injury. METHODS: Human retinal microvascular endothelial cells (HRMECs) injury was induced by culturing under hypoxic condition. The function of SAL on HRMECs injury was investigated using cell counting kit-8, 5-ethynyl-2′-deoxyuridine (EdU) staining, flow cytometry, Western blotting, and enzyme linked immunosorbent assay. MicroRNA (miR)-138, roundabout 4 (ROBO4), and proteins in the phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathways were examined using quantitative reverse transcription polymerase chain reaction or Western blotting. The target correlation was determined by dual-luciferase reporter analysis and RNA immunoprecipitation. RESULTS: Hypoxia resulted in proliferation inhibition, cycle arrest, apoptosis, inflammatory reaction, and oxidative stress in HRMECs. SAL attenuated hypoxia-induced HRMECs injury via increasing cell proliferation, and mitigating cycle arrest, apoptosis, inflammatory reaction, and oxidative stress. MiR-138 expression was enhanced by hypoxia, and decreased via SAL stimulation. MiR-138 upregulation reversed the influence of SAL on hypoxia-induced HRMECs injury. ROBO4 was targeted via miR-138. ROBO4 overexpression weakened the role of miR-138 in HRMECs injury. The PI3K/AKT/mTOR pathway was inactivated under hypoxic condition, and SAL increased the activation of PI3K/AKT/mTOR pathways by decreasing miR-138. CONCLUSIONS: SAL protected against hypoxia-induced HRMECs injury through regulating miR-138/ROBO4 axis, indicating the protective potential of SAL in retinopathies.